Pengaruh Transparansi Dan Akuntabilitas Terhadap Pengelolaan Dana Desa Di Desa Soagimalaha Kecamatan Kota Maba Kabupaten Halmahera Timur - Nurfani Salasa; Muhsin N. Bailusy; Suratno Amiro (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to determine the influence of transparency and accountability on the management of village fund in Soagimalaha Village, Kota Maba Subdistrict, East Halmahera Regency. The variables in this study consist of transparency and accountability as independent variables, and village fund management as the dependent variable. The measurement scale used in this study is the Likert scale. The research method used is a survey method with a quantitative approach, and data collection technique using questionnaires. The statistical tests used in this study are validity, reability, normality, multicollinearity, heteroscedasticity, multiple linear regression, T-test, F-test, and coefficient of determination using the Statistical Product and Service Solution (SPSS) application. The results of this study indicate that: (1) transparency partially has a positive and significant influence on village fund management, (2) accountability has a positive and significant influence on village fund management, and (3) transparency and accountability simultaneously influence village fund management with a contribution value of 52.4%. The remaining 47.6% is influenced by other factors outside the variables studied in this research.